Striae Gravidarum and Its Effect on the Quality of Life Index in Libyan Pregnant Women (Razi Medical Journal, 2025)
Striae gravidarum (SG) are common cutaneous changes during pregnancy, affecting up to 90% of women worldwide. Traditionally viewed as physiological cosmetic skin changes, emerging evidence suggests that SG may impose significant psychological distress and adversely affect quality of life (QoL). This study was conducted to evaluate the impact of SG on dermatology-specific QoL in Libyan pregnant women, taking into account established risk factors, cultural perceptions, and recent advances in therapeutic interventions. This cross-sectional study (January 2024 – December 2024) evaluated 150 pregnant women (aged ≥18) with striae gravidarum. Participants with systemic diseases or using corticosteroids were excluded. Data were collected using a self-administered online questionnaire that integrated clinical and psychosocial assessments. SG severity was determined via Davey’s scoring system, and quality of life was measured with the Skindex-16 questionnaire, validated against WHOQOL-BREF. Data analysis was performed using SPSS v25, with p < 0.05 considered statistically significant. Among 150 Libyan women with striae gravidarum (SG), 72% were aged 20–40 years, 36.7% had ≥4 pregnancies, and 64% reported a family history of SG. Participants experienced significant postpartum weight gain (73.2 ± 12.6 kg vs. pre-pregnancy 64.5 ± 10.8 kg, p < 0.001). SG was most prevalent on the abdomen (76%) and thighs (54%). Rapid weight gain (52.7%) and multiparity (32%) were perceived as leading causes. Emotional/social impacts included embarrassment (45.3%), mild self-esteem concerns (29.3%), and partner-related challenges (26.7%). Quality of life (QoL) scores (median: 16.5) were significantly higher in older women (>40 years, p < 0.001) and those with a family history of SG (p = 0.015). SG exerts a substantial negative effect on the dermatology-specific QoL of Libyan pregnant women, with pronounced impacts on emotional health and daily functioning.
Keywords: Striae gravidarum; quality of life; Libyan pregnant women; Skindex-16; stretch marks